2019
DOI: 10.1182/blood-2019-129107
|View full text |Cite
|
Sign up to set email alerts
|

Correlative Analyses of Patient and Clinical Characteristics Associated with Efficacy in Tisagenlecleucel-Treated Relapsed/Refractory Diffuse Large B-Cell Lymphoma Patients in the Juliet Trial

Abstract: Background: Tisagenlecleucel, an anti-CD19 chimeric antigen receptor (CAR)-T cell therapy, has demonstrated durable responses and a manageable safety profile in adult patients (pts) with relapsed/refractory diffuse large B-cell lymphoma (r/r DLBCL). We report the correlation of pre- and post-infusion factors and biomarkers with efficacy in tisagenlecleucel-treated pts with r/r DLBCL. Methods: Results from JULIET, a global, single-arm, pivotal, phase 2 trial of tisagenlecleucel in adult pts with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 0 publications
0
44
0
Order By: Relevance
“…The relationships between several biomarkers and efficacy of tisagenlecleucel were assessed in the overall JULIET study, and multivariate analyses identified that the high levels of LDH, a known marker of tumor burden and disease aggressiveness, at pre-infusion were associated with poor efficacy outcomes [12]. In our subgroup analysis, two non-responders and four responders also had high LDH levels at pre-infusion ( Table 1), showing that high levels of LDH at pre-infusion might not necessarily cause insufficient response in Japanese population.…”
Section: Discussionmentioning
confidence: 99%
“…The relationships between several biomarkers and efficacy of tisagenlecleucel were assessed in the overall JULIET study, and multivariate analyses identified that the high levels of LDH, a known marker of tumor burden and disease aggressiveness, at pre-infusion were associated with poor efficacy outcomes [12]. In our subgroup analysis, two non-responders and four responders also had high LDH levels at pre-infusion ( Table 1), showing that high levels of LDH at pre-infusion might not necessarily cause insufficient response in Japanese population.…”
Section: Discussionmentioning
confidence: 99%
“…Factors examined have included clinical and laboratory baseline characteristics, and the use and type of bridging therapy and lymphodepleting conditioning. When considering the 115 patients from both cohorts who were infused with tisa-cel and underwent follow-up for at least 3 months, the only baseline characteristic associated with a lower ORR in multivariate analysis was a high pre-infusion LDH level (defined as higher than twice the upper limit of normal), which is a known surrogate marker of disease burden and aggressivity (63). Of these patients, the ORR for the 11 who did not receive bridging therapy was higher than that of patients who did receive bridging therapy (82% vs. 49%), likely reflecting a lower tumor burden and less-aggressive disease in the former group (64).…”
Section: Tisa-cel For Aggressive B-cell Lymphoma Efficacy and Predictmentioning
confidence: 99%
“…In the JULIET trial, it has been reported that preinfusion elevated lactate dehydrogenase (LDH) was associated with poor outcome in patients receiving tisa-cel. 8 In clinical practice, treatment decisions are based on patient factors, including age, comorbidities, and the aggressiveness of the disease. Markers predicting adverse outcome include bulky disease, high IPI, and biological features, such as double/triple-hit cytogenetics or overexpression of MYC and BCL2 proteins.…”
Section: Introductionmentioning
confidence: 99%